Faktor-Faktor Risiko Yang Berhubungan Dengan Kejadian Gagal Ginjal Kronis Pada Pasien Rawat Jalan Di Rsud Dr Moewardi Surakarta - Munandar, Muhammad Syafiqi Aries; , Arif Widodo, A.Kep., M.Kes; , Okti Sri Purwanti, S.Kep, Ns, M.Kep .,Ns SP.Kep. MB (2016)
Chronic kidney disease is a global health problem because of the incidence and mortality continue to rise worldwide, chronic kidney disease also become a risk factor of heart disease and cancer. This study aimed to identify risk factors that relate to the incident of chronic renal failure in hospitals Dr. Moewardi Surakarta. This research is a quantitative study using cross sectional design or cross-sectional. Data obtained by providing a structured questionnaire and conducting interviews at the respondents, include age, history of hypertension,diabetes mellitus, alcohol consumption, consumption of drinks bernenergi, NSAID consumption, water consumption, the consumption of traditional herbal medicine. The data is then processed and analyzed using the chi-square test. The results showed that there is a significant relationship between chronic kidney disease with age (p=0.006, OR=2.8), history of hypertension (p=0.001, OR=55.59,diabetes mellitus (p=0.001, OR=3,29), the consumption of alcoholic beverages (p=0.003, OR=7.45, energy drink beverage consumption (p=0.001, OR=11.49,consumption of NSAID drugs (p=0.001, OR=6.29), consumption water (p=0.001, OR=4.18), consumption of traditional herbal medicine (p=0.001, OR= 3.88.